Nymphal feeding suppresses oviposition-induced indirect plant defense in rice - Jiancai Li; Xiaoli Liu; Wenhan Xiao; Jiayi Huangfu; Meredith C. Schuman; Ian T. Baldwin; Yonggen Lou (Nature Communications)
Abstract Feeding and oviposition by phytophagous insects are both known to trigger defenses in plants. Whether these two defenses functionally interact remains poorly studied, although these interactions are likely important for pests with overlapping generations. Here we investigated the differences and interaction between feeding- and oviposition-induced plant defenses triggered by the brown planthopper (BPH, Nilaparvata lugens), which gregariously feeds and oviposits on rice. Analyses of host-plant transcriptomes, phytohormones, and direct and indirect defense compounds all show that BPH gravid females (GFs), but not nymphs and non-gravid females (NFs), strongly induce rice defenses. BPH nymphs and GFs prefer to feed on plants previously infested by nymphs over un-attacked plants, but are repelled by plants previously infested by GFs. Moreover, nymph feeding is found to reduce the attractiveness of rice plants to natural enemies and decrease egg parasitism by suppressing GF-induced volatiles that mediate indirect defenses in both growth chambers and paddies. Intergenerational interactions between oviposition- and feeding-induced plant defenses not only promote the development of the population of pest insects but may also contribute to the aggregation behavior of pest insects by suppressing oviposition-induced indirect plant defenses.